AGR2: a secreted protein worthy of attention in diagnosis and treatment of breast cancer - Zhang, Ke; Li, Yuan; Kong, Xiangyi; Lei, Chuqi; Yang, Huaiyu; Wang, Nianchang; Wang, Zhongzhao; Chang, Hu; Xuan, Lixue (Frontiers in Oncology, 2023)
AGR2 is a secreted protein widely existing in breast. In precancerous lesions, primary tumors and metastatic tumors, the expression of AGR2 is increased, which has aroused our interest. This review introduces the gene and protein structure of AGR2. Its endoplasmic reticulum retention sequence, protein disulfide isomerase active site and multiple protein binding sequences endow AGR2 with diverse functions inside and outside breast cancer cells. This review also enumerates the role of AGR2 in the progress and prognosis of breast cancer, and emphasizes that AGR2 can be a promising biomarker and a target for immunotherapy of breast cancer, providing new ideas for early diagnosis and treatment of breast cancer.